The Driving Factors and Improvement Paths of CTI Integration: Based on the Spatial Dubin Model and fsQCA Method - Rongrong Liu; Jinbo Jiang (SAGE Open)
Although previous studies have explored the factors influencing cultural and tourism industry (CTI) integration, few have investigated them from a spatial and configuration perspective. Based on the panel data of 31 provinces from 2012 to 2019, the article discusses the driving factors and enhancement paths of the level of CTI integration using the spatial Durbin model (SDM) and fuzzy set qualitative comparative analysis (fsQCA). The results show that: (1) Technological innovation, consumer demand, and policy support have significant direct driving effects on CTI integration, and transportation infrastructure has a significant inhibitory effect. Market supply, transportation infrastructure, and human capital show significant spillover effects. (2) There are four paths to improve the integration level of CTI. (3) Technological innovation, market supply, and policy support perform more critical parts in CTI integration. This paper not only expands the research perspective on the driving factors of CTI integration but also applies two complementary research methods.